2019
DOI: 10.1590/1981-5271v43suplemento1-20180229
|View full text |Cite
|
Sign up to set email alerts
|

Motivação Intrínseca do Estudante de Medicina de uma Faculdade com Metodologia Ativa no Brasil: Estudo Transversal

Abstract: A cross-sectional study based on the Self Determination Theory to identify intrinsic motivation in the tutorial group scenario, and its associated factors in 276 medical students from a college in the Northeast of Brazil between October and December 2016. The Intrinsic Motivation Inventory was utilized following its adaptation and cross-cultural translation. Variables studied: age, gender, marital status, financial dependents, number of attempts at the university entrance exam for the medical course, current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
1
1
3
Order By: Relevance
“…Unlike the results obtained by Azevedo 27 , it was observed that students who lived without their parents had higher levels of motivation. In an attempt to explain this fact, one can infer that the new social reality experienced by students who are far from their families stimulates the development of autonomy, which is one of the bases of the Theory of Self-Determination.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike the results obtained by Azevedo 27 , it was observed that students who lived without their parents had higher levels of motivation. In an attempt to explain this fact, one can infer that the new social reality experienced by students who are far from their families stimulates the development of autonomy, which is one of the bases of the Theory of Self-Determination.…”
Section: Discussioncontrasting
confidence: 99%
“…The items shown in Tables 1 to 3 were analyzed through the scores obtained using the Likert scale, with a score ranging from 1 to 7. Therefore, adapted from the study by Azevedo et al 27 , the following cutoff points were used: ≤ 3.0 (low…”
Section: Methodsmentioning
confidence: 99%
“…Foram adotados os devidos termos, respeitadas suas singularidades, após esclarecimento sobre a natureza da pesquisa, justificativa, objetivos, métodos, potenciais benefícios e riscos aos participantes. Foi esclarecida a total liberdade do voluntário da pesquisa em recusar-se a 25,26 Em seguida, cada subescala/domínio foi definida por meio da média aritmética do conjunto de itens que a compunha. Foram consideradas as sete opções de respostas (1 a 7), que Considerando os fatores que influenciam a motivação intrínseca do estudante, foi comparada a motivação dos estudantes dos primeiros períodos do curso (1º, 2º e 3º) e dos últimos períodos (4º, 5º e 6º).…”
Section: Aspectos éTicosunclassified
“…No presente estudo, para todas as subescalas avaliados foram atribuídas notas >3. 26 Quanto à subescala pressão/tensão, considerada preditora negativa, a média de todos os escores foi 4,2. Presume-se que mesmo sendo uma preditora negativa, os estudantes avaliam como um ponto positivo para o método.…”
Section: Phd Scientific Review Issn 2676 -0444unclassified
“…No ambiente educacional, a motivação está diretamente relacionada ao esforço que os estudantes decidem imprimir para aprender, ao tempo que dispensam para realização de tarefas e a seu envolvimento com as atividades instrucionais. Assim, estudantes altamente motivados se engajam espontaneamente nos estudos, sem a necessidade de recompensas externas (motivação intrínseca) 2 . Por sua vez, aqueles pouco motivados dependem de recompensas externas, como o sucesso nas avaliações ou o reconhecimento de suas competências e habilidades (motivação extrínseca) 3 .…”
Section: Introductionunclassified